Gilles Deleuze's Logic of sense a critical introduction and guide - Williams, James (Russell cousin series, 2008)
This book offers the first critical study of The Logic of Sense, Gilles Deleuze's most important work on language and ethics, as well as the main source for his vital philosophy of the event. Deleuze's philosophy has always promised a revolution in ethical theories and in our understanding of the relation between language, thought and action. This book develops a critical reading of Deleuze's work in order to convey the potential and risks of his new approaches to questions of how to live an intense life in response to the excitement and danger of events. This interpretation covers all aspects
Keywords: Deleuze, Gilles, : 1925-1995 : Logique du sens; Meaning (Philosophy)